PERILAKU SISWA PENGGUNA MEDIA SOSIAL TIK-TOK DI SMP NEGERI 7 SIJUNJUNG - Fitria Yohana Restika; T. Romi Marnelly (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This research was conducted at SMP Negeri 7 Sijunjung, Sijunjung District, Sijunjung Regency. As the aims of this study are to know the froms of social behavior of adolescent who use the tiktok application and know the positive and negative impacts of tiktok social media for students who use the tiktok application. Therefore, to achieve this goal, a qualitative method was used by taking key informants from this study, namely 10 teenagers who used the Tik Tok application at SMP 7 Sijunjung. This study used a purposive sampling technique through observation and interview techniques. The results of research regarding. The results of the analysis of changes in student behavior through social media tick tock. Judging from the forms of changes in social behavior of students who use social media tiktok SMP Negeri 7 Sijunjung is the behavior of imitating and adapting things that are displayed on tiktok social media such as appearance, speaking the language used, forming social groups with a specific purpose, sorting -sort out friends according to specific goals and consumptive behavior in shopping. The positive impact of students using the TikTok application at SMP Negeri 7 Sijunjung is that students are more able to express themselves, explore their potential and discover new things. Meanwhile, the negative impact of students using the TikTok application at SMP Negeri 7 Sijunjung lies in not socializing with the surrounding environment, forming social groups based on their own goals and inviting social groups not to be active in learning. Keywords: Social Behavior, TikTok Application, Students